La tecnica INKLINK per il Museo dei Fori Imperiali nei Mercati di Traiano - Simone Boni (mediaGEO soc. coop., 2017)
The IN KLIN K gr aphic studio, with hundreds of publications and museum collaborations behind, has produced illustrations and videos for the Fori Imperiali Museum in Trajan's Mark ets.